(untitled) (Journal of Hama University, 2021)
Introduction: Sedation is a dynamic and systematic procedure intended to achieve the goals of optimum critical care management. Sedative drugs are often necessary to reduce stress and agitation, and to facilitate therapies such as mechanical ventilation. Nurses adjust sedation according to a wide range of information, including subjective assessments of patient. So the nurses must know their role in sedation management. Purpose: The aim of this study was to explore nurses’ perceptions of their role in the management of sedation in the intensive care unit in tishreen university hospital. Materials and methods: Descriptive cross-sectional study was performed using convenience sample of (n=22) nurses at tishreen university hospital in lattakia, Syria. Data were collected during the period of august to October 2020. A structured questionnaire used in the study was developed by Walker and Gillen (2006), this tool was translated to Arabic language and tested for reliability and validity, a pilot study was done on 3 nurses to test the cronbach alpha. Results: The findings of the study showed that most of nurses aware of their roll in sedation management. Three quarter of sample indicated a disagreement as follow " I will turn off the patient’s sedation if I assess that the patient no longer requires it (without an order from the doctor), I will restart sedation on a patient if I assess the patient requires it ". Conclusion and Recommendation: The results showed that the most of sample aware of their role in sedation management So, This study recommended for conduct training courses in sedation protocol and focusing on goals priority and complications.